The effect of variations in corncob activated carbon filter media with zeolite in digging well water purification - Ridwan Yusuf Lubis; Ety Jumiati; Arif Amri Panggabean (Indonesian Physics Communication, 2024)
Water is the most important element in human life, because almost all human activities require water, especially clean water which has a main function that cannot be replaced by other compounds. The aim of this research was to determine the quality of dug well water after the filtering process using corncob activated carbon and zeolite, as well as to find out which variations are optimal for obtaining clean water according to the Republic of Indonesia Minister of Health Regulation No. 32 of 2017. The strategy used to obtain clean water is the filtration technique. by organizing zeolite and activated carbon. The samples used came from Bandar Setia Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province. Activated carbon is made from corn cobs which are activated with a 10% H3PO4 solution for 24 hours. The composition of the purification system is varied into three, variation A is zeolite 75% and active carbon 25%, variation B is zeolite 50% and active carbon 50%, and variation C zeolite 25% and active carbon 75%. The greatest variation in reducing parameters in dug well water is variation A with a turbidity value of 3.7 NTU, Mn of 0.011 mg/l and KMnO4 of 5.8 mg/l. It can be explained that the results of this test are in accordance with clean water standards based on the PERMENKES Republic of Indonesia No. 32 of 2017. The results of this research that are most optimal in reducing parameters in dug well water are variation A.